FAKTOR-FAKTOR YANG MEMPENGARUHI TINGKAT KENAKALAN REMAJA (Suatu Studi di Kelurahan Kombos Barat Kecamatan Singkil Kota Manado) - Baharudin, Pusnita; Zakarias, John D.; Lumintang, Juliana (HOLISTIK, Journal Of Social and Culture, 2019)
The problem of juvenile delinquency to date can be said to have been a social problem to be faced by governments, communities and families. The reason is because the levels of adolescent delinquency lately often occur already leading to criminal action, even has been troubling the wider community.In the village of West Kombos the problem of delinquency teenagers is already a social problem, which often disrupts the public tranquility. There are various things that have led to the increase of juvenile delinquency in the region, among others, due to the lack of supportive environmental factors among many teenage children in the region who have dropped out of school so that due to poor conditions Environment, thus triggering the level of juvenile delinquency. This environmental problem also determines social polarization for adolescentsMany facts prove that there is a correlation between their criminality and other behavioral deviations; such as juvenile crimes combined with alcoholism, narcotics, radicalism, neurosis, psychopathic, promiscuity, and others. Thus a teenager who develops a habit of sociopathic behavior, usually potentially easily develops abnormal forms of behavior and other delinquent is driven by poor social stimuli or influenced by an evil social environment.The problem of juvenile delinquency in the village of West Kombos district of Singkil Manado has led to the form of social irregularities, as well as violating social norms and legal norms.Keywords: teenager, delinquent, behavior